Mapping QTLS Associated with Root Traits Related to Drought Resistance in Vietnamese Upland Rice - Nguyen Duc Thanh; Nguyen Thi Kim Lien; Pham Quang Chung; Tran Quoc Trong; Le Thi Bich Thuy; Henry Nguyen (Universitas Gadjah Mada, 2006)
Upland rice grows on 19 million ha, about 15% of the world's rice plantation [2]. The production of upland rice is crucial to agricultural economy of many countries [15]. The yield of upland rice is very low with an average of about 1 t/ha. Drought is a major constraint to the productivity of upland rice. In this paper, we present the results on mapping QTLs for root traits related to drought resistance (maximum root length, root thickness, root weight to shoot and deep root weight to shoot ratios) in upland rice using a recombinant inbreed (RI) population derived from a cross between Vietnamese upland rice accessions. The first molecular linked of Vietnamese upland rice were constructed. The map consists of 239 markers (36 SSR and 203 AFLP markers) mapped to all 12 rice chromosomes. This map covered 3973.1 cM of rice genome with an average distance of 16.62 cM between the markers. Twenty three putative QTLs were detected. Among them, four QTLs for MRL, four QTLs for R/SR, four QTLs for DR/SR, two QTL for RN, two QTLs for RT, two for PH, and five QTLs for TN were recorded. There are several SSR markers such as RM250, RM270, RM263, RM242, RM221 linked to QTL regions. They could be very useful for drought resistant selection in rice. Some common QTLs for maximum root length and deep root weight to shoot ratio were observed in different genetic background (RDB09 × R2021 and IR64 × Azorean populations) and ecological locations (IRRI and Vietnam). These QTLs could be very useful for precise locating drought resistant gene(s) and marker-assisted selection.